Pengaruh Model Pembelajaran Learning Cycle 7E terhadap Keterampilan Proses Sains Peserta Didik Kelas VIII SMPN 13 Makassar - Hasmi Hasmi; Nurhayani H. Muhiddin; Ramlawati Ramlawati (Celebes Science Education, 2024)
This study aims to determine 1) The level of science process skills scores of students taught using the Learning Cycle 7E learning model and conventional learning model, 2) The increase in the score of science process skills of students taught using the Learning Cycle 7E learning model and conventional learning model, 3) The effect of using the Learning Cycle 7E learning model on students' science process skills. This research is a Quasi-Experiment using the Nonequivalent Control Group Design. The population of all students in class VIII SMP Negeri 13 Makassar consisting of 11 classes totaling 343 students, the sample was selected by purposive sampling with 2 classes, namely class VIII I as an experimental class with 28 students and class VIII J as a control class with 27 students. Data collection is done by giving Pretest and Posttest. Data were analyzed with descriptive statistics and inferential statistics. The results of the analysis showed that 1) The level of science process skills of students taught using the Learning Cycle 7E teaching model is in the high category with an average score of 13.00 and the conventional learning model is in the medium category with an average score of 10.53, 2) The improvement of students' science process skills after being taught using the Learning Cycle 7E learning model is in the medium category with an average N-Gain score of 0.51 and the conventional model with an average N-Gain score of 0.29 is in the low category, 3) There is an effect of using the Learning Cycle 7E learning model on the science process skills of students in class VIII SMP Negeri 13 Makassar with the results of hypothesis testing, where tcount = 3.16> ttable = 1.67.